Dynamic Simulation and control of Linear Delta Robot - أسامة رزاق سالم; عرفات منصوري; ياسين سعدوني (University of El-Oued, 2022)
"The design of innovative models for smart machines dedicated to high speed manufacturing, requires the implementation of analytical and numerical models to improve the motor and dynamic behavior of the machine, taking into account the component cutting distortions and the level of control of the machine. In the context of multi-target improvement, Part I is concerned with identifying the parameters and variables inherent in each component of the thoughtful DELTA robot-type machine, the purpose of which is to improve the core elements of its structure. This requires the formulation of a multi-target problem by expressing objective functions, limitations and corresponding research spaces, as well as solving the problem through the use of high-performance mathematical methods and tools (genetic algorithms, etc.). In the second part, we will focus on the problem of effective improvement, where the device will be considered for all its components (control, structure,...) The problem of improvement (objective functions and limitations, controls and variables) will be formulated and resolved, after determining the basic components of the specifications (limitations, disciplines, solutions). In the third part, we took specific values (length and mass of the rod, engine block, rotation diameter....) And we applied it with MATLAB, we got the speed of the three engines and the power... " "يتطلب تصميم نماذج مبتكرة للروبوتات الذكية المخصصة للتصنيع عالي السرعة تنفيذ نماذج تحليلية ورقمية لتحسين السلوك الحركي والديناميكي لهذه الروبوتات، مع الأخذ في الاعتبار تغيرات القطع المكونات ومستوى التحكم في الجهاز. في سياق التحسين المتعدد الأهداف، يهتم الجزء الأول لأحدث ما توصلت إليه نمذجة الروبوتات الموازية الديناميكية ، في الجزء الثاني، سنركز على نماذج حركية وديناميكية لروبوت دلتا. في الجزء الثالث، أخذنا قيم محددة (طول وكتلة القضيب، كتلة المحرك، قطر الدوران....) وقمنا بتطبيقه مع MATLAB ، وحصلنا على سرعة المحركات الثلاثة وقيمة العزم. "
مذكرة ماستر تخصص كهروميكانيك
Keywords: multi-joint system, engineering and motor modeling, multi-target improvement, effective improvement.; "أجهزة حركية متوازية، نمذجة الهندسة والمحركات، تحسين متعدد الأهداف، تحسين فعال. "